(untitled) (World of finance, 2023)
Introduction. The new challenges and threats that engulfed Ukrainian society due to russia’s aggressive military attack on our country crystallize the new pragmatism of state-building and the rethinking of many scientific foundations of public finances. The purpose of the article is to outline the newest paradigm of the fiscal space of the state’s public finances through the prism of scientific and pragmatic approaches to taking into account the security factor in the conditions of external threats and internal challenges in Ukraine. Results. The new substantive content of the definition of the fiscal space of public finances has been substantiated. The strengths and weaknesses of the stability of the economy and public finances of Ukraine to external challenges and internal threats have been analyzed. The validation of tax and debt finances in the fiscal space of public finances of Ukraine has been studied. The vectors of probable transformations of the structure of the elements of the fiscal space are outlined in order to take into account the factor of security and stability. Prospects. Military realities in Ukraine require us to rethink both scientific postulates and practical views on the role of the state in the realm of public finances. Therefore, the subject of further scientific research is the study of the impact of endogenous and exogenous factors on the stability of public finances in the face of external threats and internal challenges, which can be assessed using the proposed pareto-optimal combination of formal and informal institutions of the fiscal space of the state.